Phubbing and impulsivity in young people aged 18 to 24 years from the Private Institute in Juliaca - Llanque Apaza, Delia (2023)
Objective: to determine if there is a significant relationship between phubbing and impulsivity in young people aged 18 to 24 years from the Private Institute in Juliaca, 2023. Methodology: it corresponds to a non-experimental, cross-sectional design, of a descriptive correlational type with a quantitative approach. 240 young people of both sexes were surveyed using non-probabilistic sampling, their ages ranged from 18 to 24 years of age. The instruments used were the Phubbing scale, this instrument reaches a confidence index of .900 and a validity of V=.98 in a total way. Regarding the Barratt Impulsivity Scale (BIS-11), it reached a confidence index of 801 and a validity  of V=.98 in a total  way. Results: there is a statistically significant relationship (Rho=-.134*; p<.0.05) between phubbing and impulsivity. Conclusion: at a high level of Phubbing in young students there will also be greater impulsiveness, said this can generate personal and family problems.